A path to a biennial life history. (October 2018) - Amasino, Richard
Biennial plants require exposure to the cold of winter to overcome a block to flowering in the spring. The molecular role of FRIGIDA, a key component of the system that establishes the cold requirement in Arabidopsis, is to assemble a protein super-complex that promotes expression of a flowering repressor in the autumn.